Quantum computation - Giannakopoulos, Dimitrios (Monterey, California: Naval Postgraduate School, 2012)
Approved for public release; distribution is unlimited. === Two seemingly unrelated scientific disciplines, information processing and quantum mechanics, were separately developed, until physicist Richard Feynman proposed their combination. Today, quantum computation is at the forefront of research in theoretical physics and computer science. The objectives of this thesis are to present an introduction to the subject of quantum computation and its potential, and to analyze the physics underlying the operation of one of the proposed realizations of a quantum logic gate, based on cavity quantum electrodynamics (QED). We discuss the fundamental aspects of quantum mechanics that may be a revolutionary new way to process information. We then present the appropriate theoretical background of QED needed to understand the proposed realization of a quantum gate. We identity the advantages and disadvantages of this realization. We then address and discuss the phenomenon of decoherence, the most fundamental obstacle to overcome for the development of practical quantum computers. Finally, some of the possible military applications are presented, along with our thoughts for the future of this field. We conclude that quantum gates based on cavity QED are feasible with current technology. However, the construction of a quantum network with these gates is not feasible, mainly due to the decoherence problems.